Complementary medicine use in US adults with hypertension: A nationally representative survey - Wiebke Kathrin Kohl-Heckl; Marleen Schröter; Holger Cramer (Elsevier, 2022)
Objectives: As well as associated cardiovascular diseases (CVD) like heart attacks, stroke, or others, arterial hypertension shows rising incidence throughout the last decades. The risk of developing an elevated blood pressure is mostly based on environmental and behavioral factors. Therefore, guidelines usually base a first-line therapy on lifestyle modifications. Complementary medicine (CM) offers a wide range of therapies to support such and CM utilization is common among CVD. We sought to analyze CM utilization among participants particularly suffering from arterial hypertension and aimed to distinguish utilization rates of different therapy approaches and predicting factors on this part of health behavior. Design and setting: This cross-sectional analysis was based on data of the 2017 National Health Interview survey (NHIS, n = 26,742; response rate 80,7%), performed among the US population. Main outcome measures and results: Within the last 12 months, 22.7% of participants reported to suffer from arterial hypertension and they were less likely to have used CM (26.8% with versus 32.5% without hypertension). Consulting a homeopath or using mind-body-medicine was more common among participants without the diagnosis, while equal proportions had consulted a chiropractor, a naturopath, a practitioner of traditional medicine, or a practitioner of chelation therapy. Regarding mind-body medicine (MBM), individuals with hypertension most often used spiritual meditation (10.6%), yoga (5.7%), mindfulness meditation (3.2%), progressive relaxation (3.1%), mantra meditation (2.4%), guided imagery (1.9%), tai chi (1.5%), and qi gong (0.4%). CM use in individuals with hypertension was associated with female sex, higher education, and/or living in the Western or Midwest USA. Conclusion: Participants with arterial hypertension were less likely to utilize CM therapies than those without. Regarding prevention and therapy of the disease, especially MBM therapies show promising results but further research and better information for the general population is needed.